Dose Dependent Antimicrobial Cellular Cytotoxicity—Implications for ex vivo Diagnostics - Copaescu, Ana; Choshi, Phuti; Pedretti, Sarah; Mouhtouris, Effie; Peter, Jonathan; Trubiano, Jason A. (Frontiers in Pharmacology, 2021)
Introduction:Ex vivo and in vitro diagnostics, such as interferon-γ (IFN-γ) release enzyme linked ImmunoSpot (ELISpot) and flow cytometry, are increasingly employed in the research and diagnostic setting for severe T-cell mediated hypersensitivity. Despite an increasing use of IFN-γ release ELISpot for drug causality assessment and utilization of a range of antimicrobial concentrations ex vivo, data regarding antimicrobial-associated cellular cytotoxicity and implications for assay performance remain scarcely described in the literature. Using the measurement of lactate dehydrogenase (LDH) and the 7-AAD cell viability staining, we aimed via an exploratory study, to determine the maximal antimicrobial concentrations required to preserve cell viability for commonly implicated antimicrobials in severe T-cell mediated hypersensitivity. Method: After an 18-h incubation of patient peripheral blood monocytes (PBMCs) and antimicrobials at varying drug concentrations, the cell cytotoxicity was measured in two ways. A colorimetric based assay that detects LDH activity and by flow cytometry using the 7-AAD cell viability staining. We used the PBMCs collected from three healthy control participants with no known history of adverse drug reaction and two patients with a rifampicin-associated drug reaction with eosinophilia and systemic symptoms (DRESS), confirmed on IFN-γ ELISpot assay. The PBMCs were stimulated for the investigated drugs at the previously published drug maximum concentration (Cmax), and concentrations 10- and 100-fold above. Results: In a human immunodeficiency virus (HIV) negative and a positive rifampicin-associated DRESS with positive ex vivo IFN-γ ELISpot assay, use of 10- and 100-fold Cmax drug concentrations decreased spot forming units/million cells by 32–100%, and this corresponded to cell cytotoxicity of more than 40 and 20% using an LDH assay and 7-AAD cell viability staining, respectively. The other antimicrobials (ceftriaxone, flucloxacillin, piperacillin/tazobactam, and isoniazid) tested in healthy controls showed similar dose-dependent increased cytotoxicity using the LDH assay, but cytotoxicity remained lower than 40% for all Cmax and 10-fold Cmax drug concentrations except flucloxacillin. All 100-fold Cmax concentrations resulted in cell death >40% (median 57%), except for isoniazid. 7-AAD cell viability staining also confirmed an increase in lymphocyte death in PBMCs incubated with 10-fold and 100-fold above Cmax for ceftriaxone, and flucloxacillin; however, piperacillin/tazobactam and isoniazid indicated no differences in percentages of viable lymphocytes across concentrations tested. Conclusion: The LDH cytotoxicity and 7-AAD cell viability staining techniques both demonstrate increased cell death corresponding to a loss in ELISpot sensitivity, with use of higher antimicrobial drug concentrations for ex vivo diagnostic IFN-γ ELISpot assays. For all the antimicrobials evaluated, the use of Cmax and 10-fold Cmax concentrations impacts cell viability and potentially affects ELISpot performance. These findings inform future approaches for ex vivo diagnostics such as IFN-γ release ELISpot.